Supporting Background, Caring Practices and Perceptions of Care in Narratives of Parents of Children Living With Autism Spectrum Disorder - Nagy, Eva (Central European Journal of Educational Research, 2025)
This study explores the childrearing practices of parents raising children with autism spectrum disorder (ASD), using D. H. Morgan’s family practices framework (Morgan, 1996, 2001, 2002, 2004, 2011), the concepts of care capital and Bowlby’s thoughts on caringscapes (Bowlby, 2012, 2017, 2019). It also addresses questions of care and autonomy within the context of disability. The author’s dual role as both researcher and parent plays a significant part in the research process. Using Grounded Theory methodology, the study involved 19 interviews with Hungarian parents of children with ASD. The findings reveal that parenting practices are shaped by the lack of formal care. Deficiencies in institutional support shift additional care responsibilities to the primary sphere of care (Lynch, 2007), intensifying parental care burdens. Parents are forced to stretch already limited resources, which can restrict both their own and their child’s experience of autonomy. Furthermore, the availability of formal care alone does not ensure a sense of agency or control for parents. Some parents with greater resources extend their roles beyond individual caregiving. They challenge dominant perceptions of autism and strive to reshape local caringscapes, effectively “rewriting” societal understandings of otherness and disability.